The level of human epididymis protein 4 is associated with poor prognosis in patients with ejection fraction preserved heart failure - Tang, Yi; Chen, Yu; Huang, Xiao Jiao; Hu, Zheng Qi; Hu, Yon Jun; Peng, Si-ling; Pan, Hong-wei (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe prognostic value of human epididymis protein 4 (HE4) in patients with heart failure with preserved ejection fraction (HFpEF) is unknown.MethodsPatients diagnosed with HFpEF in the Department of Cardiovascular Medicine of Hunan Provincial People's Hospital from January 2021 to August 2022 were prospectively enrolled in the study. Serum levels of HE4 were measured using a chemiluminescence microparticle immunoassay. Endpoint events included readmission for heart failure and cardiovascular death.ResultsA total of 170 patients with HFpEF were included in the study; among them, 86 (50.6%) were male, with a mean age of 68.9 ± 0.8 years. A total of 71 patients experienced endpoint events, including 67 patients with rehospitalizations for heart failure and 4 patients with cardiovascular deaths, with an average follow-up of 18.0 ± 0.8 months. Multivariate Cox regression analysis revealed that HE4 was an independent predictor of endpoint events (HR = 1.009, 95% CI 1.002–1.015, P = 0.010). The Kaplan–Meier survival curves revealed that the risk of endpoint events was significantly higher in patients with HE4 > 42.45 pmol/L than in those with HE4 ≤ 42.45 pmol/L (HR = 2.66, 95% CI 1.37–5.17, P < 0.01). After adjusting for age and gender, the HR was 2.48 (95% CI 1.21–5.08, P < 0.05).ConclusionHE4 is an independent predictor of heart failure rehospitalization and cardiovascular death in patients with HFpEF.